Suffering and salvation in Ciudad Juárez - Pineda-Madrid, Nancy ca. 21. Jh. (Fortress Press, 2011)
Suffering : a social reality -- Suffering, social imaginaries, and the making of evil -- Salvation : a long-standing resource -- Responding to social suffering : practices of resistance -- On the possibility of salvation